Synthesis of Nanocrystalline of Lanthanum Doped NaTaO3 and Photocatalytic Activity for Hydrogen Production - Husni Husin; Komala Pontas; Yuliana Sy; S. Syawaliah; S. Saisa (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
Sodium tantalum oxide doping lanthanum (La-NaTaO3) compounds were successfully synthesized by a sol-gel method and calcined at different temperatures. Tantalum chloride (TaCl5) was used as starting material and lanthanum nitrate (La(NO3)3.6H2O) as lanthanum source. X-ray diffraction (XRD) revealed that the calcination temperature strongly influenced the crystallinity of the prepared samples.The crystallite sizes of the resultant La-NaTaO3were in the range of 27-46 nm. The photocatalytic activities of the samples were examined for hydrogen production from an aqueous methanol solution under UV light irradiation. It was found that the photocatalytic activity of the La-NaTaO3 depended strongly on the calcination temperature. The range of calcination temperatures were 500, 700, and 900°C. The La-NaTaO3 sample calcined at 900°C showed the highest photocatalytic activity compared to the samplescalcined at the other temperatures. The rate of hydrogen production reached a value of 6.16 mmol h-1 g-1 catalyst.